Estrogen Receptor-β Mediates Estradiol-Induced Pregnancy-Specific Uterine Artery Endothelial Cell Angiotensin Type-2 Receptor Expression. Issue 4 (October 2019) - Mishra, Jay S.; te Riele, Gigi M.; Qi, Qian-Rong; Lechuga, Thomas J.; Gopalakrishnan, Kathirvel; Chen, Dong-bao; Kumar, Sathish
Abstract : The pregnancy-augmented uterine vasodilation is linked to increased AT2 R (angiotensin type-2 receptor) that mediates the vasodilatory effects of angiotensin II. However, the mechanisms controlling AT2 R expression during pregnancy remain unclear. Estrogens are known to play a role in vascular adaptations during pregnancy. We hypothesized that estrogen stimulates uterine artery AT2 R expression via ER (estrogen receptor)-β-dependent transcription in a pregnancy-specific endothelium-dependent manner. Plasma estradiol levels increased and peaked in late pregnancy and returned to prepregnant levels post-partum, correlating with uterine artery AT2 R and ERβ upregulation. Estradiol stimulated AT2 R mRNA expression in endothelium-intact but not endothelium-denuded late pregnant and nonpregnant rat uterine artery ex vivo. Consistently, estradiol stimulated AT2 R mRNA expression in late pregnant but not nonpregnant primary human uterine artery endothelial cells in vitro, which was abolished by ER antagonist ICI 182, 780. Higher ERα protein bound to ER-responsive elements in AT 2 R promoter in the nonpregnant arteries whereas higher ERβ bound in the pregnant state. ERα protein levels were similar but higher ERβ protein levels were expressed in pregnant versus nonpregnant human uterine artery endothelial cells. Estradiol stimulation recruited ERα to the AT2 R promoter in the nonpregnant state and ERβ to the AT2 R promoter in pregnancy; however, only ERβ recruitment mediated transactivation of the AT 2 R reporter gene in pregnant human uterine artery endothelial cells. Estradiol-induced AT2 R expression was abolished by the specific ERβ (not ERα) antagonist 4-[2-Phenyl-5, 7- bis (trifluoromethyl)pyrazolo[1, 5- a ]pyrimidin-3-yl]phenol (PHTPP) and mimicked by the specific ERβ (not ERα) agonist 2, 3- bis (4-Hydroxyphenyl)-propionitrile (DPN) in pregnant human uterine artery endothelial cells in vitro. This study demonstrates a novel role of pregnancy-augmented ERβ in AT2 R upregulation in the uterine artery and provides new insights into the mechanisms underlying uterine vascular adaptation to pregnancy. Abstract : Supplemental Digital Content is available in the text.